SEJARAH, KEDUDUKAN DAN FUNGSI BAHASA INDONESIA - Zulkarnain Sirait; Akmal; Edi Kurniawan; Uci Indriyani (Smart Education, 2026)
This study aims to analyze the history of language, language status, and language functions of Indonesian, as well as its transformation in the digital era. The research employs a descriptive qualitative approach supported by digital corpus analysis of 150 text data collected from social media and online platforms. The findings reveal that the Indonesian language originated from Malay and has developed into both a national and official language with symbolic, instrumental, and integrative functions. However, in digital communication practices, a significant shift in language use is observed. The data indicate that standard language usage accounts for only 38%, while non-standard forms (27%), code-mixing (19%), slang (11%), and excessive abbreviations (5%) dominate. These findings demonstrate a gap between normative linguistic standards and actual language practices in digital spaces. Nevertheless, this phenomenon also reflects the adaptability of the Indonesian language to technological developments and modern communication needs. The novelty of this study lies in the integration of language history, language status, and language functions with an empirical approach based on digital corpus analysis, as well as the introduction of the concept of digital communicative function as an extension of language function theory. This study implies the need to strengthen language literacy and adaptive language policies in the digital era.